Particulate matter and phytoplankton in the ionian sea - Rabitti, S; Bianchi, F; Boldrin, A; Daros, L; Socal, G; Totti, C (Gauthier-Villars, 1994)
Some results of a cruise carried out within the Project on the Physical Oceanography of the Eastern Mediterranean (POEM BC-091, October 1991) are reported and discussed. The major aim of this work was to study, in the upper layers of the Ionian basin the distribution of particulate matter, phytoplankton and bacteria, with emphasis on the influence of North Atlantic Water. Some tentative conclusions may be drawn from the results: the examined situation (October) is representative of the final stage of a probably annual cycle of production in an oligotrophic system; the well-developed Deep Chlorophyll Maximum between 75 and 100 m (mainly due to degradation products) does not match the biomass maximum. Possible explanations of this are: a) phytoplankton photo-adaptation processes; b) sinking to deep layer of senescent cells, relicts of previous blooms; c) grazing activity by proto- and meta-zooplankton. North Atlantic Water is probably more productive when compared with the surrounding Ionian waters during this seasonal situation, although this is still to be confirmed by data collected in connected areas, such as the Sicily Channel and the Aegean Sea.